Oral microbiome mediated inflammation, a potential inductor of vascular diseases: a comprehensive review - Gualtero, Diego F.; Lafaurie, Gloria Inés; Buitrago, Diana Marcela; Castillo, Yormaris; Vargas-Sanchez, Paula Katherine; Castillo, Diana Marcela (Frontiers in Cardiovascular Medicine, 2023)
The dysbiosis of the oral microbiome and vascular translocation of the periodontopathic microorganism to peripheral blood can cause local and systemic extra-oral inflammation. Microorganisms associated with the subgingival biofilm are readily translocated to the peripheral circulation, generating bacteremia and endotoxemia, increasing the inflammation in the vascular endothelium and resulting in endothelial dysfunction. This review aimed to demonstrate how the dysbiosis of the oral microbiome and the translocation of oral pathogen-induced inflammation to peripheral blood may be linked to cardiovascular diseases (CVDs). The dysbiosis of the oral microbiome can regulate blood pressure and activate endothelial dysfunction. Similarly, the passage of periodontal microorganisms into the peripheral circulation and their virulence factors have been associated with a vascular compartment with a great capacity to activate endothelial cells, monocytes, macrophages, and plaquettes and increase interleukin and chemokine secretion, as well as oxidative stress. This inflammatory process is related to atherosclerosis, hypertension, thrombosis, and stroke. Therefore, oral diseases could be involved in CVDs via inflammation. The preclinic and clinical evidence suggests that periodontal disease increases the proinflammatory markers associated with endothelial dysfunction. Likewise, the evidence from clinical studies of periodontal treatment in the long term evidenced the reduction of these markers and improved overall health in patients with CVDs.